Housing policy and private sector housing finance: Policy intent and market directions in South Africa. (March 2017) - Marais, Lochner; Cloete, Jan
Abstract: The introduction of homeownership for black people in urban South Africa coincided with attempts to increase mortgage finance to black households and to households in former black township areas – mostly at the lower end of the market. Government attempts to use black homeownership and mortgage finance to mitigate housing inequality in South Africa have only been partially successful. This paper traces housing policy for mortgage finance and homeownership in South Africa over a period just more than 30 years (1985–2015). Much progress has been made in providing mortgage finance to the lower end of the market, but it appears that interest rate volatility and the economic recession of 2009 (following the global financial crisis) have hampered initial progress. While more recent outcomes show indications of a thriving housing market in former black townships, the percentage of low-income households accessing small mortgages is decreasing.